How Hinge Positioning in Cross-Country Ski Bindings Affect Exercise Efficiency, Cycle Characteristics and Muscle Coordination during Submaximal Roller Skiing. - Conor M Bolger; Øyvind Sandbakk; Gertjan Ettema; Peter Federolf (PLoS ONE, 2016)
The purposes of the current study were to 1) test if the hinge position in the binding of skating skis has an effect on gross efficiency or cycle characteristics and 2) investigate whether hinge positioning affects synergistic components of the muscle activation in six lower leg muscles. Eleven male skiers performed three 4-min sessions at moderate intensity while cross-country ski-skating and using a klapskate binding. Three different positions were tested for the binding's hinge, ranging from the front of the first distal phalange to the metatarsal-phalangeal joint. Gross efficiency and cycle characteristics were determined, and the electromyographic (EMG) signals of six lower limb muscles were collected. EMG signals were wavelet transformed, normalized, joined into a multi-dimensional vector, and submitted to a principle component analysis (PCA). Our results did not reveal any changes to gross efficiency or cycle characteristics when altering the hinge position. However, our EMG analysis found small but significant effects of hinge positioning on muscle coordinative patterns (P < 0.05). The changed patterns in muscle activation are in alignment with previously described mechanisms that explain the effects of hinge positioning in speed-skating klapskates. Finally, the within-subject results of the EMG analysis suggested that in addition to the between-subject effects, further forms of muscle coordination patterns appear to be employed by some, but not all participants.